A phase 1 and randomized, placebo‐controlled phase 2 trial of bevacizumab plus dasatinib in patients with recurrent glioblastoma: Alliance/North Central Cancer Treatment Group N0872. Issue 21 (10th July 2019) - Galanis, Evanthia; Anderson, S. Keith; Twohy, Erin L.; Carrero, Xiomara W.; Dixon, Jesse G.; Tran, David Dinh; Jeyapalan, Suriya A.; Anderson, Daniel M.; Kaufmann, Timothy J.; Feathers, Ryan W.; Giannini, Caterina; Buckner, Jan C.; et al.
Abstract : Background: Src signaling is markedly upregulated in patients with invasive glioblastoma (GBM) after the administration of bevacizumab. The Src family kinase inhibitor dasatinib has been found to effectively block bevacizumab‐induced glioma invasion in preclinical models, which led to the hypothesis that combining bevacizumab with dasatinib could increase bevacizumab efficacy in patients with recurrent GBM. Methods: After the completion of the phase 1 component, the phase 2 trial (ClinicalTrials.gov identifier NCT00892177) randomized patients with recurrent GBM 2:1 to receive 100 mg of oral dasatinib twice daily (arm A) or placebo (arm B) on days 1 to 14 of each 14‐day cycle combined with 10 mg/kg of intravenous bevacizumab on day 1 of each 14‐day cycle. The primary endpoint was 6‐month progression‐free survival (PFS6). Results: In the 121 evaluable patients, the PFS6 rate was numerically, but not statistically, higher in arm A versus arm B (28.9% [95% CI, 19.5%‐40.0%] vs 18.4% [95% CI, 7.7%‐34.4%]; P = .22). Similarly, there was no significant difference in the median overall survival noted between the treatment arms (7.3 months and 7.7 months, respectively; P = .93). The objective response rate was 15.7% in arm A and 26.3% in arm B ( P = .52), but with a significantly longer duration in patients treated on arm A (16.3 months vs 2 months). The incidence of grade ≥3 toxicity was comparable between treatment arms, with hematologic toxicities occurring more frequently in arm A versus arm B (15.7% vs 7.9%) (adverse events were assessed as per the National Cancer Institute Common Terminology Criteria for Adverse Events [version 4.0]). Correlative tissue analysis demonstrated an association between pSRC/LYN signaling in patient tumors and outcome. Conclusions: Despite upregulation of Src signaling in patients with GBM, the combination of bevacizumab with dasatinib did not appear to significantly improve the outcomes of patients with recurrent GBM compared with bevacizumab alone. Abstract : In this randomized comparative phase 2 trial in patients with recurrent glioblastoma, the combination of the Src inhibitor dasatinib with bevacizumab was found to lead to a 6‐month progression‐free survival rate that was numerically but not statistically higher than that noted with single‐agent bevacizumab. The addition of dasatinib also resulted in a significantly longer response duration, but no difference in survival.